The African Charter on Human and Peoples' Rights. Nat Rubner. - Rubner, Nat, 1954- (James Currey, 2023)
A landmark study of the African Charter on human and peoples' rights, one of the most important documents in modern African history, that positions it within the African Lives Matter struggle to assert an African identity rather than as simply a human rights document. This set describes its underlying African origins and how the principles of the OAU influenced its path and content.